Hydrothermal time models for conidial germination and mycelial growth of the seed pathogen Pyrenophora semeniperda. Issue 8 (August 2015) - Barth, Connor W.; Meyer, Susan E.; Beckstead, Julie; Allen, Phil S.
Abstract: Population-based threshold models using hydrothermal time (HTT) have been widely used to model seed germination. We used HTT to model conidial germination and mycelial growth for the seed pathogen Pyrenophora semeniperda in a novel approach to understanding its interactions with host seeds. Germination time courses and mycelial growth rates for P.semeniperda were measured on PDA amended to achieve a series of five water potentials (ca. 0 to −6 MPa) at six constant temperatures (5–30 °C). Conidial germination was described with alternative population-based models using constant or variable base and maximum temperature and water potential parameters. Mycelial growth was modeled as a continuous, linear process with constant base temperature and base water potential. Models based on HTT showed reasonable fit to germination and growth rate data sets. The best-fit conidial germination model (R 2 = 0.859) was based on variable base and maximum temperature as a function of water potential. The good fit of the linear mycelial growth model (R 2 = 0.916) demonstrated the utility of HTT for modeling continuous as well as population-based processes. HTT modeling may be a useful approach to the quantification of germination and growth processes in a wide range of filamentous fungi. Highlights: Hydrothermal time has been used to model processes in seeds but not in fungi. Hydrothermal time is used here to model germination and growth in a fungus. Models for the seed pathogen Pyrenophora semeniperda parallel host seed models. Models will be used to predict disease outcome under fluctuating field conditions. The hydrothermal time approach may have wide application in filamentous fungi.